2022
DOI: 10.1094/mpmi-11-21-0270-r
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Mutualistic Mycorrhizal and Parasitic Blast Fungi Requires OsRAM2-Regulated Fatty Acid Biosynthesis in Rice

Abstract: Arbuscular mycorrhizal (AM) fungi form a mutual association with the majority of land plants, including most angiosperms of the dicotyledon and monocotyledon lineages. The symbiosis is based upon bidirectional nutrient exchange between the host and symbiont that occurs between inner cortical cells of the root and branched AM hyphae called arbuscules that develop within these cells. Lipid transport and its regulation during the symbiosis have been intensively investigated in dicotyledon plants, especially legum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
3
5
0
Order By: Relevance
“…This indicates that upregulation of lipid biosynthetic genes in AMF- treated Arabidopsis is IPD3 Min - independent, consistent with the module’s correlation to AMF treatment but not IPD3 Min expression in Figure 3A. Other genes in module O also function in lipid synthesis, including GPAT6 , a functional homolog of RAM2 which is strictly required for AM in host species (Data S3) (Gobbato et al, 2013; Dai et al, 2022). While it is a member of module O, increased GPAT6 expression was only statistically significant for AMF treatment in IPD3 Min line 308, not Col-0 or IPD3 Min 310 (Data S5).…”
Section: Resultssupporting
confidence: 71%
“…This indicates that upregulation of lipid biosynthetic genes in AMF- treated Arabidopsis is IPD3 Min - independent, consistent with the module’s correlation to AMF treatment but not IPD3 Min expression in Figure 3A. Other genes in module O also function in lipid synthesis, including GPAT6 , a functional homolog of RAM2 which is strictly required for AM in host species (Data S3) (Gobbato et al, 2013; Dai et al, 2022). While it is a member of module O, increased GPAT6 expression was only statistically significant for AMF treatment in IPD3 Min line 308, not Col-0 or IPD3 Min 310 (Data S5).…”
Section: Resultssupporting
confidence: 71%
“…Consistent with the impaired mycorrhizal phenotype, qRT-PCR results also demonstrated that the five marker genes RiTEF , OsPT11, OsAM1 , OsFatM ( fat required for AM symbiosis ) and OsRAM2 ( required for arbuscular mycorrhization2 ) ( Wang et al, 2012 ; Bravo et al, 2017 ; Jiang et al, 2017 ; Dai et al, 2022 ; Liu et al, 2022 ) were expressed at markedly reduced levels in the Ossyp131b Ossyp132 double mutants than in WT plants at both examined time points ( Figure 5C ). The relative expression level of OsSYP131a gene was not affected in the double mutants, though ( Figure 5C ).…”
Section: Resultssupporting
confidence: 66%
“…Fatty acids and their derivatives, crucial structural elements and energy materials of plant, animal, and microbial cells, are commonly found in soil, especially in the rhizosphere, where plant-derived fatty acids are accessible through root exudates and rhizodeposition (Swenson et al ., 2018; Dai et al ., 2022; Liu et al ., 2024). Building on the discovery that AMF receive fatty acids from their hosts during symbiosis, the utilization of fatty acids in the cultivation of asymbiotic AMF has received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Sugiura et al . (2020) showed that exogenous myristate (tetradecanoic acid, C14:0 fatty acid), a prevalent organic acid in various plant root exudates (Fernández-Piñar et al ., 2012; Luo et al ., 2014; Li et al ., 2017; Liu et al ., 2024) and in soil substrates (Swenson et al ., 2018; Dai et al ., 2022), can be used as a C and energy source for the asymbiotic growth of R. irregularis, promoting spore germination, hyphae growth, formation of branched absorbing structures, and the production of morphologically incomplete fertile spores. Subsequent studies revealed that the combined use of plant hormones (strigolactone and methyl jasmonate) with myristate improved the efficiency of myristate as a C and energy source in asymbiotic R. clarus , leading to the generation of numerous fertile spores that were smaller than those generated under symbiotic conditions (Sugiura et al ., 2020; Tanaka et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%